Convenções processuais e negócios imobiliários - Guedes, Fábio Tadeu Ferreira (2023)
The CPC allows the execution of atypical procedural agreements, based on art. 190, so that interested parties can make adaptations to the judicial procedure or negotiate on their procedural legal positions. The present study aims to understand what procedural agreements are, their object, positive and negative requirements and limits for the contracting parties to act. With the conceptual base formed, an attempt was made to analyze its possible applications to real estate business